A novel heat exchanger concept for latent heat thermal energy storage in solar power towers: Modelling and performance comparison. (1st November 2016) - Badenhorst, Heinrich
Highlights: Study introduces spray crystallization as phase change heat recovery option. Can be directly incorporated into tower of central power tower designs. Particle diameter found to be largest single influence of tower height. Prilling feed system identified as critical for further investigation. Best case result indicates a 20% reduction in plant capital cost is achievable. Abstract: This study presents an innovative new alternative for utilizing phase change materials as energy storage media in solar power towers. The solar power tower prilling or granulation concept combines the existing molten salt design with a prilling tower incorporated into the central receiver. In this way heat transfer limitations normally associated with these systems can be overcome since only very small particles (diameter 1–2 mm) are utilized. Three design cases were considered and a detailed model of the process was developed. The model demonstrates the design dependence on several key variables including particle diameter and the necessity of considering the system in conjunction with the steam generation cycle. Pinch considerations within this cycle and the tower itself determine the operational feasibility. It was found that the receiver design and prilling feed systems are crucial aspects which must be investigated further to refine the concept design and complete a full techno-economic assessment and optimization. The "best case scenario" resulted in a reduction of the circulating salt flow by one third compared to the base case. Preliminary indications are that this would result in a 20% reduction of the overall plant capital cost, but additional costs such as solids handling and a complex receiver design have to be taken into account.